2017
DOI: 10.1177/2378023117700651
|View full text |Cite
|
Sign up to set email alerts
|

The Organizational Trace of an Insurgent Moment

Abstract: The relationship between social movements and formal organizations has long been a concern to scholars of collective action. Many have argued that social movement organizations (SMOs) provide resources that facilitate movement emergence, while others have highlighted the ways in which SMOs institutionalize or coopt movement goals. Through an examination of the relationship between Occupy Wall Street and the field of SMOs in New York City, this article illustrates a third possibility: that a moment of insurgenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
(106 reference statements)
0
5
0
2
Order By: Relevance
“…In doing so, we join a chorus of new research on social movements that is sensitive to the relational-versus the oppositional-dynamics of protest activity. Much of this work is concentrated in empirical investigations of coalition formation among SMOs (Van Dyke & McCammon 2010, Reich 2017, Van Dyke & Amos 2017. We emphasize that our boundary-spanning processes do not just apply to an understanding of how SMO coalitions form, but also how movement actors conceptualize the breadth of their goals and the resources they can mobilize.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In doing so, we join a chorus of new research on social movements that is sensitive to the relational-versus the oppositional-dynamics of protest activity. Much of this work is concentrated in empirical investigations of coalition formation among SMOs (Van Dyke & McCammon 2010, Reich 2017, Van Dyke & Amos 2017. We emphasize that our boundary-spanning processes do not just apply to an understanding of how SMO coalitions form, but also how movement actors conceptualize the breadth of their goals and the resources they can mobilize.…”
Section: Discussionmentioning
confidence: 99%
“…Staggenborg's (2015) more recent analysis of the Group of Twenty (G20) protests in Pittsburgh also illustrates the importance of preexisting formal organizational ties, which facilitated the coordination of a broad coalition of diverse local groups opposed to the goals of the G20 meetings. By contrast, a recent investigation by Reich (2017) reverses the order of mechanisms to show how temporary co-protest ties were antecedent to the establishment of more formal alliances between SMOs. Specifically, Reich (2017) argues that the Occupy Wall Street movement was an exogenous shock that brought together activists with diverse interests for a period of intense protest.…”
Section: Organizational Boundariesmentioning
confidence: 95%
See 2 more Smart Citations
“…Today, and for the last ten years or so, issue-specific movement groups around housing, homelessness, environmental justice, healthcare, lowwage workers' rights, immigrant rights, public education, financial justice and police reform -among others -and have worked more closely with neighbourhood-based groups. Adam Reich (2017) has shown that Occupy Wall Street helped to make the networks of movement groups in New York City denser as they scrambled to contribute to, and even helped to steer, a suddenly visible and long-lasting mass protest. We analysed the membership and supporters of seven coalitions in New York City around housing (3), criminal justice (1), immigration (1), public higher education (1) and public banks (1).…”
Section: Working-class Movements In the Citymentioning
confidence: 99%